Biochemical Changes with Exogenous Cobalt Application in Soybean - P. Vijayarengan, K. Jayakumar, M.M. Azooz (Journal of Phytology, 2009)
The present investigation was executed with an objective to study the effects of Co stress in Soybean (Glycine max) with special emphasis on biochemical parameters in different parts of control as well as treated plants. In this we have analyzed the effect of cobalt (Co) stress on amino acids, proline and protein. The biochemical parameters have beneficial value at 50 mg kg-1 Co level in the soil, when compared with control. Further increase in the Co level (100-200 mg kg-1) in the soil have a negative effect on these parameters.Â  From these results it is clear that exogenous cobalt has significant role on the biochemical parameters in Glycine max.